Contact, cognition, and taiwanese youths’ attitudes toward local and Chinese culture - Yafeng Xu; Liliang You (PLoS ONE, 2026)
Classical contact theory posits that intergroup contact can reduce perceived threats and hostility between in-groups and out-groups, thereby laying the foundation for the formation of subsequent friendships and deeper forms of identification. However, in a cross-Strait context that is highly politicized and in which exchanges are deliberately obstructed by the Democratic Progressive Party, whether contact experience alone is sufficient to trigger changes in Taiwanese youths’ attitudes toward Chinese culture remains an open question requiring further examination. Drawing on data from the 2018 Taiwan Social Change Survey, this study analyzes a sample of youths aged 18–45 and constructs an index of attitudes toward “Taiwan’s local culture” to examine the effects of two independent variables, namely Taiwanese youths’ contact with the Chinese mainland and increases in Taiwanese youths’ cognition of the Chinese mainland, on their cultural attitudes. The results show that experience of contact with the Chinese mainland alone does not have a statistically significant effect on attitudes toward local culture. By contrast, individuals with higher levels of cognition of the Chinese mainland exhibit a significantly lower Taiwan’s Local Cultural Attitude Index. These findings suggest that under conditions in which cross-Strait exchanges are constrained, contact per se may be insufficient to induce shifts in cultural attitudes. Instead, its effects are more likely to operate through increases in cognition.